Pengaruh Kualitas Produk, dan Brand Image Terhadap Kepuasan Pelanggan Dan Repurchase Intention Di Hanamasa Mall Metropolitan Bekasi - Muhammad Hilmi Waliyuddin; Meylani Tuti (LPPM Universitas Asa Indonesia, 2023)
This study aims to determine the effect of product quality, and Brand Image, on Customer Satisfaction and Repurchase Intention. Respondents in this study were consumers who had come to Hanamasa Mall Bekasi. The sampling technique used was purposive sampling with 155 respondents. Data analysis used the Structural Equation Model (SEM) technique with the help of SmartPLS. The results of this study indicate that Product Quality has a significant effect on Customer Satisfaction, and Product Quality has no significant effect on Repurchase Intention. Brand image has a significant effect on customer satisfaction, and brand image has no significant effect on repurchase intention. Customer satisfaction has a significant influence on repurchase intention.